Implementation of Brain-Based Learning Approach to Increase Mathematics Learning Interest and Outcomes of Third-Grade Students - Pratama, Annisa Febriana Maulida; Ratnaningrum, Ika (International Journal of Elementary Education, 2024)
The low interest of students is caused by a less innovative approach, which makes students feel bored with learning mathematics. Low student interest in learning also has an impact on students' low mathematics learning outcomes. Based on this, this research aims to analyze the application of the brain-based learning approach to increase interest and learning outcomes in mathematics for grade III elementary school students. This type of research is qualitative research. The research method used in the quantitative research design is the ex post facto method. The population in this study was all 26 class III students. The sample for this research was all class III elementary school students, totaling 26 students. The methods used to collect data are interviews, questionnaires, documentation, and tests. The instrument used in this research was a questionnaire sheet. The data analysis technique in this research is a statistical analysis using the SPSS computer application. The results of this research show an increase in interest and learning outcomes after implementing the Brain-Based Learning (BBL) approach in mathematics learning. It was concluded that the Brain-Based Learning (BBL) approach can significantly increase interest and learning outcomes in elementary school students.